Large-eddy simulation analysis of knock in a direct injection spark ignition engine. (September 2019) - Robert, Anthony; Truffin, Karine; Iafrate, Nicolas; Jay, Stephane; Colin, Olivier; Angelberger, Christian
Downsized spark ignition engines running under high loads have become more and more attractive for car manufacturers because of their increased thermal efficiency and lower CO2 emissions. However, the occurrence of abnormal combustions promoted by the thermodynamic conditions encountered in such engines limits their practical operating range, especially in high efficiency and low fuel consumption regions. One of the main abnormal combustion is knock, which corresponds to an auto-ignition of end gases during the flame propagation initiated by the spark plug. Knock generates pressure waves which can have long-term damages on the engine, that is why the aim for car manufacturers is to better understand and predict knock appearance. However, an experimental study of such recurrent but non-cyclic phenomena is very complex, and these difficulties motivate the use of computational fluid dynamics for better understanding them. In the present article, large-eddy simulation (LES) is used as it is able to represent the instantaneous engine behavior and thus to quantitatively capture cyclic variability and knock. The proposed study focuses on the large-eddy simulation analysis of knock for a direct injection spark ignition engine. A spark timing sweep available in the experimental database is simulated, and 15 LES cycles were performed for each spark timing. Wall temperatures, which are a first-order parameter for knock prediction, are obtained using a conjugate heat transfer study. Present work points out that LES is able to describe the in-cylinder pressure envelope whatever the spark timing, even if the sample of LES cycles is limited compared to the 500 cycles recorded in the engine test bench. The influence of direct injection and equivalence ratio stratifications on combustion is also (MAPO) analyzed. Finally, focusing on knock, a Maximum Amplitude Pressure Oscillation analysis (MAPO) is conducted for both experimental and numerical pressure traces pointing out that LES well reproduces experimental knock tendencies.